2012
DOI: 10.1038/aps.2012.5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hypoxia inducible factor-1α ameliorates lung injury induced by trauma and hemorrhagic shock in rats

Abstract: Aim: Ischemia/reperfusion is an initial triggering event that leads to gut-induced acute lung injury (ALI). In this study, we investigated whether hypoxia inducible factor-1α (HIF-1α) played a role in the pathogenesis of lung injury induced by trauma and hemorrhagic shock (T/HS). Methods: Male Wistar rats underwent laparotomy and hemorrhagic shock for 60 min. Sham-shock animals underwent laparotomy but without hemorrhagic shock. After resuscitation for 3 h, the rats were sacrificed. Morphologic changes of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…Ketamine was diluted in saline at a concentration of 7.5 mg/ml and was administered at 75 mg/kg body weight. YC-1 was dissolved in 1% DMSO and was administered at 1 mg/kg 10 min after ketamine [18]. L-carnitine was dissolved in saline and was administered at 300 mg/kg 10 min after ketamine [36].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ketamine was diluted in saline at a concentration of 7.5 mg/ml and was administered at 75 mg/kg body weight. YC-1 was dissolved in 1% DMSO and was administered at 1 mg/kg 10 min after ketamine [18]. L-carnitine was dissolved in saline and was administered at 300 mg/kg 10 min after ketamine [36].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, under hypoxic conditions, HIF-1α is stabilized and translocated to the nucleus, where it dimerizes with HIF-1β and activates the expression of target genes carrying hypoxia-response elements (HREs) within their promoter or enhancer elements [17]. HIF-1 thus acts as a master regulator of cellular hypoxia response, and it can directly regulate the expression of more than 70 genes in all cell types [18]. In addition to hypoxia, non-hypoxic stimuli, such as increased ROS generation, can also increase HIF-1α expression under normoxic conditions [19,20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIF-1α promotion of lung tissue cell injury may be associated with hypoxia; the mitochondria of I/R-conditioned cells produce large amounts of reactive oxygen species, in addition to the hydroxide produced during I/R (28). A previous study in a rat model of pulmonary hypertension reported increased HIF-1α expression in the pulmonary artery intima, raising the level of downstream iNOS expression; this resulted in the proliferation of vascular endothelial cells within the pulmonary artery intima and concomitant structural damage to the pulmonary vascular endothelium, thereby promoting angiogenesis and pulmonary vascular remodeling (29). This prior study indicated that, at the protein and gene level, HIF-1α and iNOS may contribute to hypoxia, causing lung I/R injury (4).…”
mentioning
confidence: 96%
“…Most notably, the inhibition of IKK on resuscitation attenuated iNOS expression and NOx production. The reduction of the iNOS/NO pathway may contribute to the organ protection afforded by IKK16, because several strategies which reduce an excessive formation of NO also reduce organ injury (32)(33)(34)(35).…”
Section: K K I N H I B I T I O N I M P R O V E S O R G a N I N J U mentioning
confidence: 99%